Bioassay-Guided Isolation of an Antibacterial Compound from the Indonesian Soft Coral - Masteria Yunovilsa Putra; Ahmad Saparhadi; Firmansyah Karim; Tutik Murniasih; Respati Tri Swasono (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
With the aim of searching for new antibacterial compound from marine soft corals, the investigation had been conducted on antibacterial activity of an extract from soft corals Sarcophyton trocheliophorum in the n-hexane, ethyl acetate, n-butanol, and aqueous fractions. The antibacterial activity was tested against two Gram-positive bacteria, viz. Bacillus subtilis (ATCC 6633) and Staphylococcus aureus (ATCC 25923), and two Gram-negative bacteria, viz. Escherichia coli (ATCC 25922) and Vibrio cholerae (ATCC 14035) using the agar disc diffusion assay. Among them, the n-hexane fraction was the most active against three tested bacteria, viz. Bacillus subtilis, Staphylococcus aureus and Vibrio cholerae at the concentration 125 µg/ml, with inhibition zone 14.2, 18.2, 13.8 mm, respectively. Isolation and purification of the active component from the n-hexane fraction led to a known cembranoid-type diterpene, sarcophytoxide. The chemical structure of the isolated compound was determined by IR, MS and NMR, as well as compared to data from the literature. Sarcophytoxide showed moderate activity against B. subtilis, S. aureus and V. cholerae, with a minimum inhibitory concentration (MIC) of 125, 100, 125 mg/ml, respectively.